Splenic artery pseudoaneurysm with splenic infarction induced by a benign gastric ulcer: A case report. Issue 29 (July 2018) - Cho, Soo Buem; Park, Sung Eun; Lee, Chang Min; Park, Ji-Ho; Baek, Hye Jin; Ryu, Kyeong Hwa; Moon, Jin Il; Choi, Bo Hwa; Ha, Ji Young; Lee, Sangmin
Abstract: Rationale: Splenic artery pseudoaneurysm induced by benign gastric ulcer is extremely rare and can lead to a fatal clinical situation. To the best of our knowledge, there are only five cases in the literature review. Therefore, it can be a diagnostic challenge for radiologists and clinicians because of rare incidence. Patient concerns: The patient visited our hospital due to melena and dizziness. Diagnoses: The patient showed a huge ulcer and an exposed vessel in the posterior wall of the gastric high body during endoscopy. Angiography revealed a pseudoaneurysm of the splenic artery and contrast extravasation into the gastric lumen. Interventions: We performed coil embolization of splenic artery and gastrectomy. Outcomes: Postprocedural course was uneventful and led to patient discharge on day 8. Lessons: We suggest that the splenic artery pseudoaneurysm should be considered differential diagnosis in the patients with acute upper gastrointestinal bleeding, and the presence of a splenic infarction may provide a diagnostic clue.